Mild and moderate hypothermia (α-Stat) do not impair the coupling between local cerebral blood flow and metabolism in rats - Krafft, Peter; Frietsch, Thomas; Lenz, Christian; Piepgras, Axel; Kuschinsky, Wolfgang; Waschke, Klaus F. (Stroke, 2000)
Background and Purpose: The effects of hypothermia on global cerebral blood flow (CBF) and glucose utilization (CGU) have been extensively studied, but less information exists on a local cerebral level. We investigated the effects of normothermic and hypothermic anesthesia on local CBF (LCBF) and local CGU (LCGU). Methods: Thirty-six rats were anesthetized with isoflurane (1 MAC) and artificially ventilated to maintain normal Paco2 (α-stat). Pericranial temperature was maintained normothermic (37.5°C, n=12) or was reduced to 35°C (n=12) or 32°C (n=12). Pericranial temperature was maintained constant for 60 min until LCBF and LCGU were measured with autoradiography. Twelve conscious rats served as normothermic control animals. Results: Normothermic anesthesia significantly increased mean CBF compared with conscious control animals (29%, P<0.05). Mean CBF was reduced to control values with mild hypothermia and to 30% below control animals with moderate hypothermia (P<0.05). Normothermic anesthesia reduced mean CGU by 44%. No additional effects were observed during mild hypothermia. Moderate hypothermia resulted in a further reduction in mean CGU (41%, P<0.05). Local analysis showed linear relationships between LCBF and LCGU in normothermic conscious (r=0.93), anesthetized (r=0.92), and both hypothermic groups (35°C r=0.96, 32°C r=0.96, P<0.05). The LCBF-to-LCGU ratio increased from 1.5 to 2.5 mL/μmol during anesthesia (P<0.05), remained at 2.4 mL/μmol during mild hypothermia, and decreased during moderate hypothermia (2.1 mL/μmol, P<0.05). Conclusions: Anesthesia and hypothermia induce divergent changes in mean CBF and CGU. However, local analysis demonstrates a well-maintained linear relationship between LCBF and LCGU during normothermic and hypothermic anesthesia.